El pago por Cesión de bienes como medio de extinguir las obligaciones y su incidencia frente al Contrato de Préstamo de Mutuo, en la Corporación Financiera Nacional, Sucursal Riobamba, en el año 2014” - Morales Bravo, Jhonatan Javier (2016)
loan contract, whether civil or commercial, expresses an obligation that must be satisfied by the borrower in order for the lender to return any collateral assets offered to secure the loan. Should any irregularities arise after the execution of the contract, then possible liability for breach of contract may have occurred. Any necessary refund should occur under the terms of the contract with respect to the obligations noted within the contract itself. Any necessary and acceptable refund should generally be of equal value and acceptable under the terms of the contract. If an obligation cannot be extinguished under the terms of the contract, then the Civil Code provides for the power to dispose, to liquidate, or to transfer any collateral assets from the borrower, if needed, to satisfy the terms of the contract. Additionally, under Article 1635 of the Civil Code, if the debt is not adequately satisfied then the creditors are entitled to pursue any remaining debt, usually at the expense of the borrower which can sometimes greatly increase the final costs to the borrower. The Civil Code also provides for the possibility that the debtor may possibly regain their property, in the event that the contract is somehow satisfied and it is not necessary to dispose, to liquidate, or to transfer any collateral assets from the borrower to the lender.